Magnesium and type 2 diabetes mellitus: Clinical and molecular mechanisms - Luis Soriano-Pérez; Ana Karina Aranda-Rivera; Alfredo Cruz-Gregorio; José Pedraza-Chaverri (Health Sciences Review, 2022)
Type 2 diabetes mellitus (T2DM) is one of the most common chronic diseases, affecting hundreds of millions of people worldwide. Environmental factors influence the progressive development of diabetes, the main ones being obesity, hypertension, dyslipidemia, and genetic factors. In addition to the above factors, magnesium (Mg2+) deficiency has been linked to an increased risk of developing T2DM in the general population. The homeostasis of this ion is highly regulated by absorption in the intestine, storage in bone, and renal excretion. However, Mg2+ content in the diet, the primary source for the body, and the content of Mg2+ in fruits and vegetables have progressively decreased, so Western-style diets currently contain between 30 and 50% of the minimum recommended magnesium. Since Mg2+ deficiency has been associated with higher fasting glucose concentrations, glycosylated hemoglobin, or higher insulin resistance rates in patients with T2DM, Mg2+ supplementation may be a potential therapy to treat T2DM. Although Mg2+ deficiency has been widely studied in T2DM, the molecular clinical and molecular mechanisms are poorly reviewed. This review examines the recent literature linking T2DM to altered Mg2+ homeostasis, from experimental observations and clinical trials to the molecular mechanisms by which Mg2+ influences glucose homeostasis in T2DM.